Education to employment : Designing a system that works - Mourshed, Mona [Verfasser]; Farrell, Diana [Verfasser]; Barton, Dominic [Verfasser] (My University, 2013)
"Around the world, governments and businesses face a conundrum: high levels of youth unemployment and a shortage of job seekers with critical skills. How can a country successfully move its young people from education to employment? What are the challenges? Which interventions work? How can these be scaled up? These are the crucial questions. In this report, we attempt to answer them. To do so, we developed two unique fact bases. The first is an analysis of more than 100 education-to-employment initiatives from 25 countries, selected on the basis of their innovation and effectiveness. The second is a survey of youth, education providers, and employers in nine countries that are diverse in geography and socioeconomic context: Brazil, Germany, India, Mexico, Morocco, Saudi Arabia, Turkey, the United Kingdom, and the United States. We started this research recognizing the twin crises of a shortage of jobs and a shortage of skills. In the course of it, though, we realized we needed to take into account another key shortage: the lack of hard data. This deficiency makes it difficult to even begin to understand which skills are required for employment, what practices are the most promising in training youth to become productive citizens and employees, and how to identify the programs that do this best." (Hrsg.; BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; S 5.3 Personalentwicklung; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; I 2.2.1 Westeuropa; I 2.3.3 Lateinamerika; I 2.3.4 Asien; I 2.3.1 Afrika; I 2.3.2 Nordamerika; Junger Erwachsener; Berufseinmündung; Jugendarbeitslosigkeit; Qualifikationsanforderung; Qualifikationsentwicklung; Arbeitsmarktchance; Brasilien; Bundesrepublik Deutschland; Indien; Mexiko; Marokko; Türkei; Saudi-Arabien; Vereinigtes Königreich; USA